2012
DOI: 10.3184/095422912x13491962881734
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and speciation analysis of organotin compounds

Abstract: The use of antifouling paints in shipbuilding has led to a significant concentration of organotin compounds in the marine environment. Antifouling paints have become the main source of tributyltin and triphenyltin derivatives loaded into the sea. The toxicity of organotin compounds has been of great concern. High concentrations of organotin compounds are associated with growth abnormalities in mussels and oysters and have also resulted to the decline in their abundance. High concentration of organotin compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Later research revealed that the TBT sorption in sediment is characterized by a rapid reversible adsorption stage, where 80% of the final sediment concentration is adsorbed within 10 min (Langston and Pope, 1995;Champ and Seligman, 1996), and a slow, non-reversible stage of TBT diffusion into the porous microstructure of the organic material (Pignatello and Xing, 1996;Ma et al, 2000). A similar instant adsorption process was observed in soil while TBT was not easily leached off (Sunday et al, 2012). The sorption of the majority of the neutral TBT hydroxide form, in sediments from coastal waters at average pH 8 to the organic carbon in the sediment might be the principal process.…”
Section: Tbt: Distribution Bioavailability and Uptakementioning
confidence: 88%
See 2 more Smart Citations
“…Later research revealed that the TBT sorption in sediment is characterized by a rapid reversible adsorption stage, where 80% of the final sediment concentration is adsorbed within 10 min (Langston and Pope, 1995;Champ and Seligman, 1996), and a slow, non-reversible stage of TBT diffusion into the porous microstructure of the organic material (Pignatello and Xing, 1996;Ma et al, 2000). A similar instant adsorption process was observed in soil while TBT was not easily leached off (Sunday et al, 2012). The sorption of the majority of the neutral TBT hydroxide form, in sediments from coastal waters at average pH 8 to the organic carbon in the sediment might be the principal process.…”
Section: Tbt: Distribution Bioavailability and Uptakementioning
confidence: 88%
“…In seawater at average pH 8 and ionic strength 0.5M 93% of the TBT in solution occurs as the hydroxide complex (Arnold et al, 1997), likely favored by the hydrolyzable nature of TBTO, TBT halides and TBT acetate (Eng et al, 1986). The halides were estimated to have a half-life of 60 days in aqueous media (Sunday et al, 2012) while biodegradation half-lives as low as 6 days have been reported in clean harbor water (Cooney, 1988;Adelman et al, 1990). The predominant occurrence of TBT hydroxide in marine systems was an important indication to link the partitioning behavior of TBT to that observed for neutral hydrophobic substances and predictions based on the K ow equilibrium partitioning (Meador, 2000).…”
Section: Tbt: Distribution Bioavailability and Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Although the biological functions of Sn have not been described to date, it is difficult to agree with the opinion that Sn is a nonessential metal that is of no importance to organisms [15,16]. Sn compounds affect the physiology of bacteria and fungi [17][18][19][20][21], plants [13,14], and animals [15,17,22,23]. Interactions of Sn with microorganisms are ambiguous, as although Sn and its compounds can be metabolized by some microorganisms, they are toxic to others.…”
Section: Introductionmentioning
confidence: 99%
“…Organotin (OTs) compounds are the organometallic pollutants, where aryl or alkyl groups are chemically bonded to tin (Sn). The number and structure of the organic moieties bonded to Sn can significantly alter its physicochemical properties [1][2]. The industrial and agricultural utility of phenyltin compounds has led to the presence of it in food products and environment, resulting into a wide spread risk of human exposure.…”
Section: Introductionmentioning
confidence: 99%